Karakteristik kimia dan fisik tablet effervescent kombinasi kopi robusta dan jahe emprit dengan variasi konsentrasi serbuk kopi jahe dan jenis asam - Marcella Berliana Purnama; Umar Hafidz Asy'ari Hasbullah; Rini Umiyati; Arief Rakhman Affandi (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Coffee is a drink favored by the broader community because of its distinctive taste. One of the kinds of coffee drinks consumed widely is instant ginger coffee. Ginger coffee has the advantage of natural antioxidant potential. It is necessary to innovate new products that are more practical and accepted by consumers and served with cold water, namely tablet effervescent drinks. The purpose of this research was to investigate the effect of the concentration of ginger-coffee powder and variations in the organic acid on the chemical and physical properties of effervescent tablets. The ginger-coffee powder was made by crystallization with a ratio of 1:1 of them. Tablet effervescent formulated with two kinds of acid, i.e., tartaric acid, malic acid, and a combination. The results showed that increasing ginger-coffee powder concentration significantly decreases moisture content, IC50, hardness, and lightness (L*). In contrast it significantly increased acid content, phenolic content, redness (a*), and yellowness (b*). Tablet with a combination of tartaric acid and malic acid has lower IC50, hardness, and lightness. In contrast, it has higher phenolic compounds, redness, and yellowness. The best formula formaking ginger-coffee effervescent tablets was a concentration of 50 % ginger-coffee powder with a combination of tartaric acid and malic acid.